Pelatihan Analisis Viskositas untuk Mengoptimalkan Kinerja Pompa Positive Displacement dalam Produksi Susu - Tungki Yufa Paradana; Munandar, Megara (Dharmakayana, 2025)
This community service program was implemented to enhance the competency of production operators in understanding and applying viscosity analysis to optimize the performance of positive displacement pumps in the sweetened condensed milk (SCM) production process. Based on pump performance data obtained from the production area, an increase in fluid viscosity from 1000 to 2000 cP significantly impacted flow reduction, increased motor load, decreased efficiency, and overall operational performance decline. This condition indicates the need for structured training for operators to understand the relationship between viscosity, temperature, and pump parameters. The activities conducted included theoretical training, field practice, implementation of new SOPs, and evaluation of pump performance before and after the SOP. The evaluation results showed an average pump efficiency increase of 11.4% and a motor load reduction of 12–25%, particularly under high viscosity conditions. The operator can identify the optimal viscosity, adjust the inverter frequency based on the recommendation table, and independently perform performance analysis. Thus, this program is effective in enhancing production process efficiency and strengthening human resource competencies in the sweetened condensed milk production line.